Multiphase phosphide cocatalyst for boosting efficient photocatalytic H2 production and enhancing the stability. Issue 1 (1st January 2021) - Liu, Song; Huang, Jinxing; Su, Haiwei; Tang, Guogang; Liu, Qinqin; Sun, Jingfang; Xu, Jing
Abstract: Constructing appropriate cocatalysts to modify semiconductors is significant for improving photocatalytic H2 production and stability. Transition metal phosphides (TMPs) with low-cost and high efficiency have been considered as one of the most promising non-noble-metal cocatalysts. Herein, a novel multiphase phosphide nanosheet, Fe2 P/Ni3 P cocatalyst, was target designed and in-situ incorporated with Cu2 O nanocubes via a phosphorization method for photocatalytic H2 evolution under visible light irradiation. The optimal Cu2 O/Fe2 P/Ni3 P sample provided 10-folds higher photocatalytic activity of H2 evolution rate (108.68 μmol g−1 h−1) than that of single Cu2 O (18.6 μmol g −1  h −1 ), which could be ascribed to fast charge transfer from the Cu2 O to multiphase phosphide Fe2 P/Ni3 P cocatalyst and efficient separation of the light-induced charge carriers. Moreover, the Fe2 P/Ni3 P cocatalyst also improved the photo-corrosion of Cu2 O caused by the disproportionation reaction, leading the Cu2 O/Fe2 P/Ni3 P hybrid possessed robust stability. Additionally, this work guarantees useful insights in employing novel TMPs-based cocatalysts to construct visible-light-responsive photocatalysts, which manifests promising applications in the dwindling supply of energy.